Washington food artisans : farm stories and chef recipes - Bloom, Leora Y. (Sasquatch Books, 2012)
"Two of the biggest draws of the farmers' market are the chance to buy local products and the opportunity to meet the producer--to skip the middleman and shake the hand of the farmer, the forager, the artisan. For so many of us living in the city, shopping at the supermarket, unwrapping plastic-covered sandwiches for lunch, or grabbing quick takeout, the vendors are heroic. They are passionate about their products and have chosen to do what they do on a small scale for any number of reasons, including better quality, tradition, respect for the earth, or to continue a family business. Writer Leora Bloom profiles 17 such Washington food artisans, including producers of fruit, wine, cheese, tomatoes, lavender, and honey, as well as meat, fish, and grains. She also provides recipes for each farmer's products, procured from Washington's most renowned chefs and restaurants"--